Hot and Cold Seasons in the Housing Market - Ngai, L. Rachel; Tenreyro, Silvana (American Economic Review, 2014)
Every year housing markets in the United Kingdom and the United States experience systematic above-trend increases in prices and transactions during the spring and summer (“hot season”) and below-trend falls during the autumn and winter (“cold season”). House price seasonality poses a challenge to existing housing models. We propose a search-and-matching model with thick-market effects. In thick markets, the quality of matches increases, rising buyers' willingness to pay and sellers' desire to transact. A small, deterministic driver of seasonality can be amplified and revealed as deterministic seasonality in transactions and prices, quantitatively mimicking seasonal fluctuations in UK and US markets. (JEL C78, R21, R31)